Effects of Thyrotropin-Releasing Hormone (TRH) on the Actions of Pentobarbital and Other Centrally Acting Drugs - Breese, George R. (1975)
Thyrotropin-releasing hormone (TRH) was found to antagonize pentobarbital-induced sleeping time and hypothermia. While 3 to 100 mg/kg of TRH reduced pentobarbital sleeping time when administered prior to the barbiturate, a dose-response relationship to TRH could not be established. However, doses of 10 to 100 mg/kg of TRH enhanced the lethality of pentobarbital when these compounds were administered simultaneously. Thyrotropin or l-triiodothyronine did not imitate and hypophysectomy did not reduce the effects of TRH, indicating that the pituitary is not essential for its antagonism of pentobarbital Studies of TRH analogs provided further support of this view In addition TRH reduced the sleep and hypothermia produced by thiopental amobarbital, seco-barbital and phenobarbital, and it antagonized the hypothermia and reduced motor activity produced by chloral hydrate, reserpine, chlorpromazine and diazepam Intracisternally administered TRH also reduced pentobarbital sleeping time and hypothermia but melanocyte-stimulating hormone release-inhibiting factor and somatostatin administered by this route did not While reduction of pentobarbital sleeping time by TRH could not be attributed to an affect on monoamine systems or to deamidated TRH, this action was reduced by intracisternally administered atropine suggesting that cholinergic mechanisms may contribute to the effects of TRH. Thus the results provide evidence that TRH acts on brain independent of an effect on the pituitary.